2018
DOI: 10.3892/etm.2018.6072
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone reduces spinal cord injury by inhibiting inflammatory response, oxidative stress and apoptosis via PPAR‑γ and PI3K/Akt pathways

Abstract: The present study used a mild contusion injury in rat spinal cord to determine that thymoquinone reduces inflammatory response, oxidative stress and apoptosis in a spinal cord injury (SCI) rat model and to demonstrate its possible molecular mechanisms. The rats in the thymoquinone group received 30 mg/kg thymoquinone once daily by intragastric administration from 3 weeks after surgery. Hematoxylin and eosin staining, Basso, Beattie and Bresnahan (BBB) scale and tissue water content detection were used in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…For example activities of caspases like caspase-3, caspase-9 or cleaved caspase -3 are studied as hall marks of apoptosis in cancer cells (Gupta et al, 2018a, Gupta et al, 2018b). Treatment of TQ in spinal cord injury reduces the activity of caspase-3 and caspase-9 and inhibited apoptosis in an animal model (Chen et al, 2018) and the same mechanism has also been reported in gastric carcinoma (Gali-Muhtasib et al, 2004).…”
Section: Thymoquinone and Apoptosismentioning
confidence: 57%
“…For example activities of caspases like caspase-3, caspase-9 or cleaved caspase -3 are studied as hall marks of apoptosis in cancer cells (Gupta et al, 2018a, Gupta et al, 2018b). Treatment of TQ in spinal cord injury reduces the activity of caspase-3 and caspase-9 and inhibited apoptosis in an animal model (Chen et al, 2018) and the same mechanism has also been reported in gastric carcinoma (Gali-Muhtasib et al, 2004).…”
Section: Thymoquinone and Apoptosismentioning
confidence: 57%
“…41 The ability of PPAR-γ to exert anti-inflammatory effects has been extensively studied, [42][43][44] Moreover, activation of PPAR-γ exerts anti-inflammatory effects via inhibiting the transcription factors, such as activator protein-1 and nuclear factor-kB. 46 What' more, PPAR-γ is expressed in various cell types including astrocytes, microglia and neurons in the brain, and PPAR-γ activation in microglia leads to reduce the production of pro-inflammatory cytokines by these cells. 45 Chen et al demonstrated that thymoquinone inhibits spinal cord injury via preventing inflammatory response, apoptosis and oxidative stress through PPAR-γ and PI3K/Akt pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a parallel pathway, TQ has also been shown to induce the expression of pro-apoptotic proteins via PPAR-γ in breast cancer cell lines [92]. TQ has been reported to induce the expression of PPAR-γ in diverse cellular contexts [92,93]. In breast cancer cells, TQ-mediated activation of PPAR-γ leads to the downregulation of the expression of the pro-survival genes Bcl-2 and BCL-xL [92].…”
Section: Tq-mediated Inhibition Of Cancer Cell Survivalmentioning
confidence: 99%